Economic and Political Results of the Russian Federation WTO Membership: Assessment on the Base of International Organizations Theories - E. V. Zhiryaeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article some international organizations theories predictions are examined on the results of Russia’s accession to the WTO. Import indicators have improved after accession: import diversification has grown and import concentration has reduced. There was no influence on export as the first ten export positions of the Russian Federation are raw materials. The payment matrix of a game with nonzero sum has been applied to the analysis of anti-dumping measures in bilateral trade with China, Ukraine and the EU. The strategy «to join the WTO» was shown to be optimal for Russia. The strategy «to admit Russia to the WTO» was optimal for the EU and Ukraine, but not for the China. We don’t confirm the argument that the trade agreement is directed to protectionism restriction as the number of anti-dumping measures in mutual trade of the Russian Federation has grownafter the WTOaccession. The advanced countries, as it was shown, keep a high difference in access of certain goods to the markets. It has a sense to estimate extent of liberalization according to an indicator of import concentration. From this point of view, market access provided by Russia was higher than in the advanced economies since 2005. Countries do can carry out liberalization unilaterally. E.D. Mansfield and E.E. Reinhardt have shown that the country as a member of the regional trade agreement improves its bargaining power. This conclusion in our work has been extended to a case of the country participation in the WTO. It was shown that the trade regime of the Russian Federation hasn’t suffered after 2014. At the same time taking into account the effect of «improvement of a bargaining power», which was revealed in literature for the stage of the regional trade agreement, the EEU is offered to include in its agenda territorial development and transport tariffs matters.